48.3k views
3 votes
Plzzzzzzzzzzzz help fast

Plzzzzzzzzzzzz help fast-example-1

2 Answers

4 votes

y = 2x^2 - 4

Add both side 4

y + 4 = 2x^2 - 4 + 4

y + 4 = 2x^2

Divide both sides by 2

( y + 4 ) ÷ 2 = 2x^2 ÷ 2

y + 4 / 2 = x^2

x^2 = y + 4 / 2

x = + √(y+4/2) Or x = - √(y+4/2)

Thus the second option is the correct answer.

User Chris Kent
by
5.1k points
2 votes

COPYING IS NOT AT ALL GOOD MY BOY ! TRY TO CHANGE THAT HABIT

User Bernd Rabe
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.